2017
DOI: 10.22159/ajpcr.2017.v10i12.20560
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mahkota Dewa (Phaleria Macrocarpa) (Scheff.) Fruit Pericarp Extract on Inos in Mice Colon Intermittently-Induced by Dextran Sodium Sulfate

Abstract: Objective: The objective of this research was to investigate the anti-inflammatory effect of Mahkota Dewa fruit pericarp extract (Phaleria macrocarpa) on inducible nitric oxide synthase (iNOS) in mice colon induced by dextran sodium sulfate (DSS). Method:The simplisia of P. macrocarpa pericarp was weighed (1000 g) and extracted by maceration process. The total yield of the ethanolic extract was 26.43%. Phytochemical screening was carried out for the detection of the phytoconstituents by simple qualitative meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…The effect of P. macrocarpa on inflammation is shown by previous studies. This study showed an inhibition of the expression of iNOS protein in the cryptic colon epithelial cells induced by DSS [8,9]. The incidence of inhibitory effects is also in line with the increase in the extract dose of P. macrocarpa.…”
Section: Discussionsupporting
confidence: 52%
“…The effect of P. macrocarpa on inflammation is shown by previous studies. This study showed an inhibition of the expression of iNOS protein in the cryptic colon epithelial cells induced by DSS [8,9]. The incidence of inhibitory effects is also in line with the increase in the extract dose of P. macrocarpa.…”
Section: Discussionsupporting
confidence: 52%
“…According to Kusmardi et al, the type of flavonoid contained in PM, kaempferol, was thought to be one of the factors that upregulate Caspase-3 expression. 35 Henry et al also state that kaempferol-induced apoptosis is related to its ability to change the expression of apoptotic markers, such as caspase-3 (caspasedependent) and AIF (caspase-independent). 36 In conjunction with apoptosis, Kaempherol increases the levels of pro-apoptotic enzymes and proteins, such as cleaved caspase-9, -7, -3, p21, p53, Bax, PARP, and p-ATM and decreased the levels of anti-apoptotic proteins Bcl2, pololike kinase 1 (PLK-1), and pAKT.…”
Section: Effect Of Pmlee On Caspase-3 Expressionmentioning
confidence: 99%
“…The mice colon tissues that were used in this research has been processed into a biological material or paraffin block from prior research correlated to the topic. The effect would be histopathologically observed and planned as a comparison, parallel, and randomly using the same process that have been used previously by Kusmardi et al and Suprapti et al 25,26 This research was done after ethical approval from The Health Research Ethics Committee, Faculty of Medicine, Universitas Indonesia, with ethical number of : 0891/ UN2.F1/ETIK/2018…”
Section: Methodsmentioning
confidence: 99%